Managerial Ownership, Corporate Monitoring and Audit Pricing - HAN, Soongsoo (Sam) (Institutional Knowledge at Singapore Management University, 2008)
We study whether managerial ownership and corporate monitoring (board quality and analyst coverage) relate to audit pricing. Managerial ownership has been identified as a fraud risk factor under SAS 99. However, the role of ownership is not clear. Under an alignment view, high levels of stock ownership align management with shareholders. Under an entrenchment view, high levels of ownership may motivate management to be self interested. Corporate monitoring, as measured by analyst coverage and overall board quality (Gomper’s index), are associated with information quality. Audit pricing will be affected to the extent that auditors perceive monitoring as being relevant to managers’ reporting incentives. Our tests use a large sample over the period of 2000-2004 and control for regulatory changes over that period. Our results indicate that lower fees are associated with higher levels of management ownership. We also find a negative relationship between fees and measures of corporate monitoring.